2017
DOI: 10.1007/s10877-017-9994-1
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity affect the non-invasive measurement of cardiac output performed by electrical cardiometry in children and adolescents?

Abstract: Electrical cardiometry (EC) is a non-invasive and inexpensive method for hemodynamic assessment and monitoring. However, its feasibility for widespread clinical use, especially for the obese population, has yet to be determined. In this study, we evaluated the agreement and reliability of EC compared to transthoracic Doppler echocardiography (TTE) in normal, overweight, and obese children and adolescents. We measured stroke volume (SV) and cardiac output (CO) of 131 participants using EC and TTE simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Those full-text articles were assessed for eligibility, which led to 24 included studies and 17 excluded studies [18,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. The included studies were divided into 13 studies in adults [28][29][30][31][32][33][34][35][36][37][38][39][40] and 11 studies in pediatrics [41][42][43][44][45][46][47][48][49][50][51]. Contacting the manufacturer and screening of the reference lists of all included studies led to no additional studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those full-text articles were assessed for eligibility, which led to 24 included studies and 17 excluded studies [18,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. The included studies were divided into 13 studies in adults [28][29][30][31][32][33][34][35][36][37][38][39][40] and 11 studies in pediatrics [41][42][43][44][45][46][47][48][49][50][51]. Contacting the manufacturer and screening of the reference lists of all included studies led to no additional studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Concerning adult studies; two were conducted in the OR during liver transplantation surgery [31,39], three during cardiac surgery [28,29,36], two both during cardiac surgery and post cardiac surgery in the ICU [30,33], two in the ICU [35,40], three in the cardiology unit [34,37,38] and one in the outpatient unit [32]. Concerning pediatric studies; four were conducted in the OR [45,47,49,50], two in the ICU [43,44], two in the neonatal intensive care unit (NICU) [46,51], and three in the outpatient unit [41,42,48]. The ICON ® device was used in nine studies [28, 29, 31, 32, 41-43, 45, 48] and the Aesculon ® in fifteen studies [30, 33-40, 44, 46, 47, 49-51].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Narula et al 12 conducted a study in children with a variety of structural congenital heart defects and concluded that ICON provides a reliable noninvasive estimation of CO. In another pediatric study Altamirano‐Diaz et al 13 found strong correlations for CO and SV measured simultaneously with ICON and transthoracic echocardiography, with the exception of obese patients, where electrovelocimetry tended to underestimate CO and SV.…”
Section: Methodsmentioning
confidence: 94%
“…Electrical cardiometry has the advantage of being non-invasive, simple, user-friendly, and does not need expensive disposables. Electrical cardiometry was previously evaluated in the operating room in human patients [15], [20]; as well as animals [12].…”
Section: Discussionmentioning
confidence: 99%